If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x+3)=2(3x+10)
We move all terms to the left:
4(2x+3)-(2(3x+10))=0
We multiply parentheses
8x-(2(3x+10))+12=0
We calculate terms in parentheses: -(2(3x+10)), so:We get rid of parentheses
2(3x+10)
We multiply parentheses
6x+20
Back to the equation:
-(6x+20)
8x-6x-20+12=0
We add all the numbers together, and all the variables
2x-8=0
We move all terms containing x to the left, all other terms to the right
2x=8
x=8/2
x=4
| (x)=6x+7 | | 8x=11x-16 | | 5(3x+11)=175 | | 3(4c+1)+9=24 | | -(x-1)+8=9 | | -3x+12=2x+32 | | 10x+2(6/13)=-16 | | -9^2−14=f(9) | | (u-8)+7=25 | | 13)-6=b/18= | | -6x-8=40 | | -30x^2+65x+40=0 | | 15h−3h+–1=–19 | | |x|-11=-7 | | -139=-3(5+1)-2x | | 13-(2c+2)=2(c+3)+3c | | 5+7n=15+3n | | 2b+5=b+13= | | 2(4-5k)=5(2-k) | | 5+5-6x7=x | | 8x7=x | | 15x-6=6x-x | | -3/5-1/2x=1/3 | | -5=7u+6(u-3) | | -4(z–12)=42 | | 3x-1÷2=7 | | -23=3x+4(x+3) | | 141=13x+4+10x-1 | | 5(v-2)+7v=26 | | -11-5/6a=1/10(5a+4) | | 15x-9=15-5 | | 0.2x+0.6=0.9x-0.8 |